REKONSTRUKSI PEMBELAJARAN SEJARAH MELALUI PROJEK BASED LEARNING (PjBL) di SMA SAINTEK BS UHAMKA - Hari Naredi; Ahmad Ruslan; wardahsamiah (KARMAWIBANGGA Historical Studies Journal, 2023)
This study aims to examine the innovations needed by history learning in the face of negative stigma regarding history learning which is considered uninteresting. The intended learning innovation is the reconstruction of history learning through the application of the Project Based Learning (PjBL) model. This research uses descriptive qualitative methods by emphasizing the use of literary sources, both books and articles related to major themes. The results of this study show that the use of the Project Based Learning (PjBL) learning model at SMA Saintek Boarding School Uhamka which focuses on the involvement of students in completing projects that relate solving solutions to the realities of everyday life and are relevant to the problems faced by students. Involvement in the implementation of learning can shape the character of students and change the stigma of history learning which is considered uninteresting.